2023
DOI: 10.1021/acsami.3c03275
|View full text |Cite
|
Sign up to set email alerts
|

On-Chip Liquid Manipulation via a Flexible Dual-Layered Channel Possessing Hydrophilic/Hydrophobic Dichotomy

Abstract: The hydrophilic/hydrophobic cooperative interface provides a smart platform to control liquid distribution and delivery. Through the fusion of flexibility and complex structure, we present a manipulable, open, and dual-layered liquid channel (MODLC) for on-demand mechanical control of fluid delivery. Driven by anisotropic Laplace pressure, the mechano-controllable asymmetric channel of MODLC can propel the directional slipping of liquid located between the paired tracks. Upon a single press, the longest transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…As shown in Figure a, a mixed organic droplet of 5 μL was deposited on top of the parallel channel. The mixed organic drops in the parallel channel were completely separated within 68 s. Researchers found that water droplets can be transported rapidly and directedly from the nonparallel channel’s open side (the root of SHMW) to the corner (top of SHMW). , As shown in Figure b, the mixed organic droplet was deposited on the open side of the nonparallel channel and transported both octane and glycol to the top of the nonparallel channel. Although the nonparallel channel can achieve ultrafast transport of liquid droplets, mixed organic droplets cannot be separated by the nonparallel channel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure a, a mixed organic droplet of 5 μL was deposited on top of the parallel channel. The mixed organic drops in the parallel channel were completely separated within 68 s. Researchers found that water droplets can be transported rapidly and directedly from the nonparallel channel’s open side (the root of SHMW) to the corner (top of SHMW). , As shown in Figure b, the mixed organic droplet was deposited on the open side of the nonparallel channel and transported both octane and glycol to the top of the nonparallel channel. Although the nonparallel channel can achieve ultrafast transport of liquid droplets, mixed organic droplets cannot be separated by the nonparallel channel.…”
Section: Resultsmentioning
confidence: 99%
“…The asymmetrically tapered structure of the cactus enables the rapid transportation and collection of water droplets for its growth. Inspired by these biologically self-transporting droplet methods, the study of open surface-based spontaneous fluid transport has been widely reported, providing new ideas for microfluidics, liquid collection, and separation processes. Spontaneous fluid transport based on open surfaces can be realized for oil–water separation, emulsion separation, and other related processes. Based on the repeated opening and closing action of the beak when shorebirds drink water, Lou et al. achieved a microscale oil–water mixture separation by squeezing the mixture using two nonparallel plates .…”
Section: Introductionmentioning
confidence: 99%
“…Driven by the anisotropic Laplace pressure, droplets can move directionally in the MODLC. The maximum transmission distance can reach 10 cm and the average speed is about 3 cm/s when a single compression is performed . Such a directional transport structure is conducive to fog collection. , Drawing inspiration from the predation behavior of shorebirds, a branch-structure elastic three-dimensional space fabric with a structure similar to that of the beak of shorebirds is developed (Figure b).…”
Section: Bionic Fog Collection Surfacesmentioning
confidence: 99%
“…Current research focuses on the development of bilayer membranes thanks to their high potential for moisture transportation by individually altering the composition and structure of each layer. 7,8 The bilayer membranes, also known as Janus membranes, are usually composed of a hydrophobic inner layer and a hydrophilic outer layer. 9 The asymmetric wettability in the thickness direction can achieve the effect of one-way directional water transportation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This functionalized textile drives sweat from the skin while it can restrain the opposite permeation. Current research focuses on the development of bilayer membranes thanks to their high potential for moisture transportation by individually altering the composition and structure of each layer. , The bilayer membranes, also known as Janus membranes, are usually composed of a hydrophobic inner layer and a hydrophilic outer layer . The asymmetric wettability in the thickness direction can achieve the effect of one-way directional water transportation. The hydrophilic layer in the Janus membrane mainly relies on a driving force to guide water transport, and the small pore size is conducive to rapid water transport (capillary transport).…”
Section: Introductionmentioning
confidence: 99%